Understanding barriers and benefits to adopting elephant coexistence practices in oil palm plantation landscapes in Lower Kinabatangan, Sabah - Othman, Nurzhafarina; Mustapah, Muhammad Al-Shafieq; Quilter, Aida Ghani; DeWan, Amielle (Frontiers in Conservation Science, 2022)
Oil palm managers are one of the key stakeholders who could help strengthen efforts to protect elephants in the landscape. We used a Theory of Change (ToC) approach to hypothesize potential barriers and benefits to managers adopting best practices. We conducted two focus groups with more than 60 participants to better understand managers' perceptions of Human-Elephant Conflict (HEC) and their willingness to adopt better wildlife management practices. The focus group confirmed that some of the outcomes we perceived in the original ToC, including security issues, false accusations, negative perceptions by the international community, and crop damage, were affecting their willingness to promote coexistence in their plantation. However, we also uncovered other potential barriers and opportunities to promote coexistence, including international and national standards that do not provide enough technical and practical guidance for all levels, expensive monitoring costs, and inconsistent collaboration among industry players and between government and non-government agencies. Our initial findings suggest that new attitudes and perceptions have not been explored before and may be critical for manager engagement and adoption of best practices for HEC, as well as the identification of new audiences that would need to be engaged to be successful in achieving elephant conservation goals.